2020
DOI: 10.1080/23311975.2020.1824440
|View full text |Cite
|
Sign up to set email alerts
|

Islamic index, independent commissioner and firm performance

Abstract: The prime objective of this study is to examine the effect of Sharia firms and their performance in Indonesia. Sharia is the set of personal and societal behaviour derived from Islam. A firm is included in a sharia firm if it complies with Islamic values. The sample used in this study are firms that are consistently listed on the Shariacompliant Stock Index (ISSI) in the 2012-2018 period. The result shows that Sharia firms have better performance compared to non-Sharia firms. Additionally, Sharia firms with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Based on the criteria, there are 15 Islamic banks from 3 countries (Indonesia, Malaysia and Bahrain) with total data are 135 data. Those countries are the top ten countries which have many consumers in the halal industry for certain sectors (Gati et al, 2020). Table 3 describes the statistics descriptive of the variables.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Based on the criteria, there are 15 Islamic banks from 3 countries (Indonesia, Malaysia and Bahrain) with total data are 135 data. Those countries are the top ten countries which have many consumers in the halal industry for certain sectors (Gati et al, 2020). Table 3 describes the statistics descriptive of the variables.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Capital structure is measured using the ratio of total debt to total assets (DTA), corporate governance is measured by two variables, namely the number of independent commissioners (IC) and institutional ownership (IO). (Evana, 2020); (Phuong et al, 2022); (Gati et al, 2020) Source: Data processed, 2022…”
Section: Resultsmentioning
confidence: 99%
“…One of their duties is to supervise and represent the interests of minority shareholders, so that their role is expected to have a positive impact on the Company and shareholders. Abidin, (2009); Kiptoo et al, (2021); Phuong et al, (2022); dan Gati et al, (2020) revealed that independent commissioners have a positive influence on firm performance. However, another study found that the existence of independent commissioners has no influence on performance, it happens when directors have less than optimal performance (Karim & Purwanto, 2020;Prabowo & Simpson, 2011;Setiawan et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Organizations that follow sharia procedures outperform their non-sharia compliant counterparts (Gati et al, 2020). However, the influence of Islam's diversity on organizational success is still up for debate (Hassan & Marimuthu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…If a company adheres to Islamic ideals, it is classified as a sharia organization, and sharia-compliant organizations outperform the non-sharia compliant organizations. Sharia positioning may boost performance, and they provide actual proof that the ethical firm has a substantial impact on outcomes (Gati et al, 2020).…”
Section: Sharia-compliant Organizationmentioning
confidence: 96%